The associations of the triglyceride-glucose index and its combination with blood pressure on cardiovascular and all-cause mortality in hypertension: a national study - Xu, Jun-Peng; Peng, Xiong-Qiang; Guo, Li-Heng; Zhao, Xu-Jie; Chen, Mao-Sheng; Mai, Xiao-Yi; Tan, Jia-Wei; Chen, Quanfu; Zeng, Rui-Xiang; Zhang, Min-Zhou (Frontiers in Endocrinology, 2024)
The triglyceride-glucose (TyG) index, a reliable surrogate biomarker of insulin resistance (IR), is highlighted recently as related to cardiac disorders. However, the associations of the TyG index and its combination with blood pressure (BP) on cardiovascular and all-cause mortality in hypertension remain unclear. In this study, we included 9,635 hypertension patients from the National Health and Nutrition Examination Survey 1999–2018. During a median follow-up of 8.00 years, a total number of 853 and 2,489 in cardiovascular and all-cause deaths occurred, respectively. After full adjustments, the individual TyG index was positively associated with cardiovascular and all-cause mortality with J-shaped dose–response relationships. The lowest risk thresholds of the TyG index for cardiovascular and all-cause mortality were 9.5551 and 9.3405, respectively. In joint analyses, the highest risks of cardiovascular and all-cause mortality were observed among those with elevated levels of both BP and IR [1.64 (1.18, 2.28), P = 0.0031; 1.39 (1.14, 1.70), P = 0.0011; respectively]. In sensitivity and subgroup analyses, the results were generally robust. Our data appeal a hypothesis that future treatments for hypertension may require a combination of BP controlled and IR improvement.